THE SEAFLOOR MORPHOLOGHY OF SUNDA STRAIT FOR LAYING THE UNDERWATER CABLES - Yogi Noviadi (Marine Geological Institute of Indonesia, 2010)
The coastal and offshore areas around the Sunda Strait will be developed to be a submarine cable corridor connecting between Java and Sumatra Islands. There are some requirements that should be considered before laying the underwater cables. One of these considerations is to understand the seafloor morphology of the Sunda Strait. The study was conducted based on six of track lines with 1 km line spacing and 4 Cross lines. The water depth obtained then was corrected to the depth of water from the Lowest Water Level (LWL). The seabed condition in the near shore area of Sumatra side is very flat and is influenced by 2 km offshore tide activity. The coast line is characterized by mangrove and fine fraction of sediments (mud and clay). At the Java side, the coastal morphology is characterized by the very steep slope and most of the area is occupied by the industrial activities. Keywords: seafloor morphology, under water cables, Sunda Strait Area pantai dan perairan Selat Sunda akan dikembangkan sebagai bagian dalam penempatan kabel bawah laut yang menghubungkan Pulau Jawa dan Pulau Sumatera. Rencana penempatan kabel bawah laut ini membutuhkan beberapa persyaratan teknis yang harus dipertimbangkan. Salah satu pertimbangan untuk peletakan kabel bawah laut adalah memahami morfologi dasar laut selat Sunda. Penelitian dilakukan berdasarkan 6 lintasan pemeruman dengan jarak antar lintasan 1 km, dan 4 lintasan memotong lintasan utama. Kedalaman laut yang diperoleh kemudian dikoreksi dengan muka laut terendah. Kondisi permukaan dasar laut di sisi pantai Sumatra sangat datar serta sejauh 2 km ke arah laut lepas masih dipengaruhi oleh aktifitas pasang surut. Garis pantainya dicirikan oleh tanaman bakau dan fraksi sedimen halus (lumpur dan lempung). Pada sisi Jawa, morfologi pantai dicirikan oleh kemiringan lereng yang curam dan kebanyakan area ditempati oleh aktivitas industri. Kata kunci: morfologi dasar laut, kabel bawah laut, Selat Sunda